Pengaruh Work Life Balance Stres Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada UMKM Sarining Serati di Kabupaten Gianyar - Lestari, Ni Kadek Yuni; Pratama, Octavianus Sumardana; Nindia Putri, Cokorda Istri Agung Vera; Idayanti, I Dewa Agung Ayu Eka (BUDGETING : Journal of Business, Management and Accounting, 2024)
Employee performance is one that determines the success of achieving organizational goals. The performance of employees of UMKM Sarining Serati in Gianyar Regency found a phenomenon of lack of accuracy from employees which resulted in customer complaints against UMKM Sarining Serati in Gianyar Regency. Factors that cause employee performance to decline due to work life balance work stress and work environment. The formulation of the problem in this study is how is the partial and simultaneous influence between work life balance, work stress and work environment on employee performance at UMKM Sarining Serati in Gianyar Regency? The purpose of the study was to determine the partial and simultaneous influence between work life balance work stress and work environment on employee performance at UMKM Sarining Serati in Gianyar Regency. This study has a population of 38 and a sample of 38 employees. Furthermore, quantitative analysis consists of classical assumption test, multiple linear regression analysis, determination analysis, t-test statistical analysis and F-test statistical analysis. The results showed that partially work life balance has a negative and significant effect on employee performance. partially work stress has no negative and insignificant effect on employee performance. Partially work environment has a positive and significant effect on employee performance. work life balance work stress and work environment have a significant effect simultaneously on employee performance. Keywords: Work Environment And Employee Performance, Work Life Balance, Work Stress.